2020
DOI: 10.1155/2020/4297483
|View full text |Cite
|
Sign up to set email alerts
|

Crocin Alleviates Pain Hyperalgesia in AIA Rats by Inhibiting the Spinal Wnt5a/β-Catenin Signaling Pathway and Glial Activation

Abstract: At present, most of the drugs have little effect on the pathological process of rheumatoid arthritis (RA). Analgesia is an important measure in the treatment of RA and is also one of the criteria to determine the therapeutic effects of the disease. Some studies have found that crocin, a kind of Chinese medicine, can effectively alleviate pain sensitization in pain model rats, but the mechanism is not clear. Emerging evidence indicates that crocin may inhibit the metastasis of lung and liver cancer cells from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 60 publications
2
22
0
Order By: Relevance
“…After HD administration, rats showed reduced pain sensitivity in mechanical allodynia and thermal hyperalgesia. Our data are in line with the literature, which reports that activation of WNT/β-catenin signaling contributes to increasing pain sensitivity [46]. Next, we explored the mechanism underlying pain development triggered by the activation of Wnt signaling.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…After HD administration, rats showed reduced pain sensitivity in mechanical allodynia and thermal hyperalgesia. Our data are in line with the literature, which reports that activation of WNT/β-catenin signaling contributes to increasing pain sensitivity [46]. Next, we explored the mechanism underlying pain development triggered by the activation of Wnt signaling.…”
Section: Discussionsupporting
confidence: 89%
“…HD treatment reduced WNT3a and FZ8 expression and β-catenin accumulation in the cytosolic and nuclear compartments. While upstream activation of β-catenin is triggered by WNT-binding FZ receptors, downstream WNT/β-catenin activation regulates the activity of proinflammatory mediators, such as IL-18, TNF-α and IL-1β, which may directly contribute to the onset and persistence of pain [45,46], as demonstrated by behavioral alterations. HD showed important anti-inflammatory activities by reducing IL-18, TNF-α and IL-1β levels, downregulating the inflammation associated with pain.…”
Section: Discussionmentioning
confidence: 99%
“…However, with the establishment of AIA, a significant decrease in withdrawal threshold in AIA group could be observed, and this phenomenon was consistent with studies reported. 70 , 71 Theoretically, KETO, as an excellent analgesic drug, should show its anti-nociception effect when subcutaneous injected at the dosage of 2–5 mg kg −1 q24h in rats. 72 , 73 However, the limited anti-nociception effect was observed in this study even though we delivered the KETO at dosage of 10 mg kg −1 , which was potentially due to the administration intervals was changed from q24h to q72h.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that some signaling pathways can affect the progression and prognosis of RA, including Wnt/β-catenin signaling pathways. The Wnt/β-catenin pathway can regulate inflammatory cytokine secretion, which can affect fibroblast-like synoviocyte (FLS) proliferation and give rise to bone metabolism/destruction (Brunt et al, 2018; Liang et al, 2019 ; Macedo et al, 2019 ; Wang et al, 2020 ; Miao et al, 2021 ). When the Wnt signaling pathway is activated, pro-inflammatory cytokines, including TNF-α and IL-1β , are produced ( Wu et al, 2017 ; Brunt and Scholpp, 2018 ; Yuan et al, 2018 ).…”
Section: Role Of Crocin In Bone and Cartilage Diseasesmentioning
confidence: 99%